(untitled) (Multidisciplinary Journal of Science and Technology, 2024)
Mechatron devices of management pneumatic hydraulic of types used without PLC controller on the side devices automatic process organize to reach see​ we went out Then no results that’s it showed that devices quickness in providing manage devices optimization seeing we went out